Rethinking the Political Economy of Environmental Conflict: Lessons from the UK Fracking Controversy - Adam Patrick Marshall (Manchester Metropolitan University, e-space, 2023)
As governments and corporations have intensified their efforts to locate, extract, and capitalise oil, gas, and various other biophysical materials, the world has simultaneously witnessed a proliferation of social resistance to these efforts. While taking many forms, such resistance, and concomitant ecological distribution conflicts (EDCs), are invariably motivated by a diverse range of objections regarding the unequal distributions of power, harms, and benefits associated with these extractive endeavours. This thesis primarily addresses the EDC literature, an environmental justice activist orientated literature at the intersection of ecological economics and political ecology. Despite offering numerous insights regarding the socio-metabolic drivers of EDCs, this literature often tends towards problematic explanations regarding the role of capitalist power. Thus, while these explanations foreground questions of capitalist power, their core assumptions - especially the analytical distinction between `the political' and `the economic'- serve to elide key aspects of capitalist power within this context. Moreover, they also tend to obscure an important counterpart to capitalist power of special relevance to the activists who mobilise for environmental justice within EDCs; namely, capitalist vulnerability. Consequently, this thesis enfolds existing EDC insights within a broader theoretical framework underpinned by the Capital as Power (CasP) approach to political economy. CasP's overarching contribution is to enable researchers to map how intra-capitalist conflicts unfold through the reorganisation of social ecological relations. Mobilising this framework, and a unique combination of qualitative and quantitative methods in the context of the UK fracking conflict (2010-2020), this thesis aims to explore, understand, and explain capitalist power and vulnerability in fracking conflicts (specifically) and EDCs (generally). Alongside other key findings, the inherent uncertainty surrounding future earnings and the divergent interests of competing capitalist coalitions are identified as key sources of capitalist vulnerability that environmental justice activists can exploit within EDCs. These findings highlight the analytical benefits of a CasP-driven theoretical framework for elucidating capitalist power and vulnerability in fracking conflicts and EDCs, not only for activists and academics, but also for policy makers, businesses, and other advocates for just transformations towards sustainability.
Keywords: P; P1; P12; P18; Q3; Q4; Q5; 330; activism; capital as power; capitalist vulnerability; conflict; fracking; ecology; energy; environment; shale gas; UK